Unique technological competencies and requests for external innovation - new diversification mechanisms and management objects in the innovation sphere - KASHIRIN, A.I.; KASHIRIN, P.A. (The journal of contemporary issues in business and government, 2020)
The study of trends in the development of the world economy showed that the formation in the near future of new global markets in the research and production sphere and the corporate sector, actively interact with each other. That can be named as the market of technological competencies and the market of problems and tasks. The role and place of technological competencies, as well as problems and tasks, as new objects of management in the innovation sphere are determined. The concepts of “unique technological competencies” and “requests for external innovations” are formulated. The basis of the latter are the problems and tasks of business. In addition to the term “key competencies of a company” that has become established in modern scientific literature, a new “unique technological competence of a team of specialists” has been introduced, in addition, a new concept is proposed in the form of “owner of a problem or task”, which together represent new subjects of management in the innovation sphere. It has been established that “unique technological competencies of teams” are the essential basis of the Centers of Global Excellence and Centers of Global Competitiveness, and measuring organizations in terms of the number and quality of such centers they have is a new approach to assessing the potential for innovative development. On the basis of practical examples, it is shown that the creation of management systems for these objects and entities opens up new, previously almost never used, ways of diversification and commercialization.